Global Review of Grievance Redress Mechanisms in World Bank Projects - World Bank (Washington, DC, 2014)
Effectively addressing grievances from people impacted by World Bank projects is a core component of managing operational risk and improving a project s results. Grievance redress mechanisms (GRMs) can be an effective tool for early identification, assessment, and resolution of complaints on projects. Understanding when and how a GRM may improve project outcomes can help both project teams and beneficiaries improve results. However, there is little data available on the prevalence, quality, or impact of GRMs in existing World Bank projects. This note provides a snapshot of current usage of GRMs in World Bank projects, a qualitative assessment of selected GRMs, and recommendations for improved risk management via GRM implementation and design. The goal of the review is to provide project staff and managers with: (i) a quantitative overview of current GRM application in project design; (ii) qualitative assessment of GRM implementation issues; and (iii) recommendations for improved risk management via GRM design and implementation.